Development of an integrated CAD/CAE/CAM system for forging process: a proposal - Abdullah, Ahmad Baharuddin; Hamouda, Abdel Magid Salem (2005)
Forging can be described as the process in which metal is plastically deformed with application of huge pressure. The process not only changes the shape but also improves the properties of the forged parts due to grain size refinement. Conventionally, the empirical trial and error method has been applied, but recently there are various tools are employed to improved product quality and economic of the process. For example, Computer Aided Design (CAD) is widely used in modeling of the process, while Computer Aided Engineering (CAE) tools have been utilized in analyzing the process. To physically demonstrate the process, Computer Aided Manufacturing (CAM) such as CNC machine has been exploited. In order to improve forging process efficiency, an integrated system that combines all advantages of CAD, CAM and CAE need to be developed. This paper presents a proposal of new system that integrate CAD, CAE and CAM to assist the designer in producing forged parts.